2004
DOI: 10.18388/abp.2004_3564
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of total, free and protein bound thiols as well as sulfane sulfur in different age groups of rats.

Abstract: The redox status of plasma thiols can be a diagnostic indicator of different pathological states. The aim of this study was to identify the age dependent changes in the plasma levels of total, free and protein bound glutathione, cysteine and homocysteine. The determination was conducted in plasma of three groups of rats: 1) young (3-month-old), 2) middle aged (19-month-old), and 3) old (31-month-old). Total levels of glutathione, cysteine and homocysteine and their respective free and protein-bound fractions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…A similar age-dependent decline in plasma tHcy levels was observed in apoE Ϫ/Ϫ mice fed methionine-enriched control or high-fat diets (36). Previous studies in rats (37) also showed that plasma levels of total, free, and protein-bound thiols, including homocysteine, decreased with age. These observations suggest that the age-dependent decline in plasma tHcy could be related to the induction of genes involved in intracellular homocysteine metabolism and/or export.…”
Section: Discussionsupporting
confidence: 68%
“…A similar age-dependent decline in plasma tHcy levels was observed in apoE Ϫ/Ϫ mice fed methionine-enriched control or high-fat diets (36). Previous studies in rats (37) also showed that plasma levels of total, free, and protein-bound thiols, including homocysteine, decreased with age. These observations suggest that the age-dependent decline in plasma tHcy could be related to the induction of genes involved in intracellular homocysteine metabolism and/or export.…”
Section: Discussionsupporting
confidence: 68%
“…, 2008). Total sulfhydryl or thiol (T‐SH) content of the plasma is another parameter in evaluating the oxidative damage of proteins in plasma because 80% of plasma sulfhydryl content was reported to originate from plasma proteins (Iciek et al. , 2004; Candiano et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the levels of total plasma LMWT in rats are 75-200 µmol/l (Cys), 5-22 µmol/l (GSH) and 3.2-14.4 µmol/l (Hcy) [29][30][31]. It should be noted that age and diet (B 9 , fatty acid consumption) have a great impact on the total LMWT levels [30,32].…”
Section: Discussionmentioning
confidence: 99%